Menakar Yang Kreatif dalam Demokrasi Komunikatif - Laku, Silvester Kanisius (Sapientia Humana: Jurnal Sosial Humaniora, 2024)
This paper discusses creativity within Iris Marion Young's communicative democracy. The analysis of creativity in Young's communicative democracy focuses on the tension between the informal communication model proposed by Young through everyday communication such as greetings, rhetoric, and narrative (storytelling), and the procedural and rational argumentative models in deliberative democracy. On one hand, the rational argumentative model is considered the best way to achieve consensus, but on the other hand, this model is seen as betraying the participation of ordinary people who generally not only lack access to power structures but also have limited rational capabilities. Young's communicative democracy model is viewed as an alternative way to address this practical deadlock. This paper aims to present a new perspective in the field of political philosophy about an alternative way of thinking that may overcome the procedural rigidity in deliberative democracy. The method used in writing this paper is descriptive and critical analysis, which aims not only to provide an overview of the ideas of communicative democracy and the tensions surrounding these ideas, but also to explore the possibility of linking communicative democracy with an understanding of creativity. The findings suggest that Young's communicative democracy is best understood as creativity in democracy for the purpose of justice for all.